INFLUENCE OF LASER EXPOSURE ON THE PHYSICAL PROPERTIES OF NANO V2O5 FILMS GROWN BY THERMAL EVAPORATION - Fatehmulla, Amanullah; Aslam, M.; Farooq, W. A.; Ali, Syed Mansoor; Atif, M.; AlDhafiri, A. M.; Yakuphanoğlu, Fahrettin (Springer, 2016)
It is shown that the nanostructures of vanadium pentoxide (V2O5) obtained by laser treatment of films grown by thermal evaporation differ significantly in their properties from analogues based on V2O5. Results of XRD and SEM studies show the increase in grain size with the increasing intensity of the laser radiation, and spectral analysis data indicate a decrease in the band gap.
Keywords: thermal evaporation; nano V2O5; laser irradiation; red shift; bandgap tailoring